A Mathematical Illustration of Why It’s Good for Long-term Investors to Buy Wonderful Companies at Fair Prices - Samsa, Greg (Archives of Business Research, 2019)
One of Warren Buffett’s many insights on investment is often rendered as: “It’s far better to buy a wonderful company at a fair price than a fair company at a wonderful price.” We illustrate some of the mathematics behind this aphorism. More specifically, we illustrate the returns associated with purchasing stock in a company which compounds its earnings per share at a constant annual rate of 15% (i.e., the economic component of total return), at a price-earnings ratio of 20, and sold at different time points at different price-earnings ratios (i.e., the speculative component of total return). The primary result is that, over time, the relative contribution of the economic component of the total return increases relative to the speculative component. The Buffett strategy appropriately focuses on the economic component of long-term returns. This result can be applied to investing in mutual funds as part of a long-term retirement portfolio, and the demonstration used to illustrate the potential benefits and risks of purchasing diversified mutual funds during a bubble.